The Study on Blockchain Adoption Strategies for Pharmaceutical Regulatory Products Under Dual-Channel Competition - Jianan Chen; You Xiao; Nianxing Yuan; Yong Wang; Jiamin Zhang; Lihui Wang (IEEE Access)
In the global pharmaceutical industry, dual-channel competition has become a common business model, where the synergy and competition between online and offline channels profoundly impact corporate strategic decision-making. This study constructs a dual-channel competition model for pharmaceutical regulatory products to explore blockchain adoption strategies and analyze their impact on corporate profits. Four adoption scenarios are defined: both online and offline channels do not adopt blockchain (NN), offline adopts while online does not (BN), online adopts while offline does not (NB), and both online and offline channels adopt blockchain (BB). The methodology involves developing mathematical models for each scenario using parameters such as pricing, demand, and profit, followed by deriving equilibrium decisions for each model. Optimization techniques are used to solve for the optimal pricing and demand under the defined scenarios. Additionally, numerical analysis is conducted using hypothetical parameter values to evaluate the influence of factors like market potential demand, price sensitivity, and the negative impact of non-adoption. The findings reveal that the BB model consistently achieves the highest profit growth and resilience, demonstrating that full adoption of blockchain technology across both channels provides maximum benefits. Conversely, partial adoption (BN or NB) shows moderate improvement, while non-adoption (NN) leads to significant profit losses. This study highlights that adopting blockchain technology in dual-channel supply chains not only improves transparency, safety, and consumer trust but also optimizes profitability and risk resistance. For resource-constrained firms, a phased adoption strategy—starting with the more profitable channel—is recommended to gradually enhance operational efficiency and market competitiveness.